Expression of vimentin, E-cadherin and TGF-β as markers of epithelial-mesenchymal transformation and criteria for the prognosis of the diseaseby epithelium in benign pathology and prostate gland cancer - Tkachenko, P. V.; Yakovtcova, I. I.; Dolgaya, O. V.; Ivakhno, I. V. (Journal of Education, Health and Sport, 2017)
Epithelial-mesenchymal transformation in prostate gland cancer is a criterion of aggressive biological behavior of the tumor, but the clinical material is not sufficiently studied. The objective of the research was to study epithelial-mesenchymal transformation and its prognostic significance in benign pathology and prostate gland cancer. The absence of vimentin expression and the evident reaction of E-cadherin in the epithelium in benign pathology of the prostate glandwere revealed. The change in the expression of these markers in prostate gland canceroccur at the expense of low-differentiated forms and is characteristic of the high-risk group (p <0.05 and p <0.01, respectively). An inverse dependence between the reaction of vimentin and E-cadherin (p <0.05) and their correlation withTGFβ (p <0.05) was detected. Conclusion: community of the molecular-biological manifestations of the epithelial-mesenchymal transformation in prostate gland cancer and involvement of TGFβ into its process has been proved. Epithelial-mesenchymal transformation maybe a prognostic criterionof the disease.